PENGARUH VARIASI KERAPATAN SPORA Beauveria bassiana DAN KONSENTRASI LCPKS TERHADAP MORTALITAS LARVA Oryctes rhinoceros - Nurari Yani; Muhammad Arif Fadhillah; Julaili Irni (Agro Estate, 2019)
Oryctes rhinoceros beetle is one of the pests that attacksimmature oil palm plants.This pest attacks oil palm plants in larvae or imago phase. This pest is usually damaging the respiratory roots, trunk bark, dry petiole,or periphery crown of oil palm leaves which can interferes the leaf growth and finally reduce the production even collapse the tree. Chemically pest control have the positive impact with faster pest death beside the negative impacts such as resistance, resurgence, disturbing human health and also environmental and ecosystem pollution. Biological control is one alternative pest control that is safe for the environment and can reduce chemical residues in agricultural products and environment. This study was conducted in Medan Denai district on July – Agustus 2019. This study aimed to determine the effect of the use of Beauveria bassiana and palm oil mill effluent to control Oryctes rhinoceros larvae. The method used in this study is a two factorial randomized block design (RBD), with 2 replications. The results of this study showed that the best density of Beauveria bassiana spores in controlling Oryctes rhinoceros larvae was 109 spores / ml and 50ml LCPKS (I2Q2) with death time of 40 hours, daily mortality 60%, total mortality 100%